2017
DOI: 10.1002/14651858.cd012599
|View full text |Cite
|
Sign up to set email alerts
|

First and second trimester serum tests with and without first trimester ultrasound tests for Down's syndrome screening

Abstract: Tests involving first trimester ultrasound with first and second trimester serum markers in combination with maternal age are significantly better than those without ultrasound, or those evaluating first trimester ultrasound in combination with second trimester serum markers, without first trimester serum markers. We cannot make recommendations about a specific strategy on the basis of the small number of studies available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 578 publications
0
29
0
1
Order By: Relevance
“…Recent advances in imaging techniques, medical genetics and clinical biology have enabled clinicians to screen for various adverse outcomes, such as aneuploidy, pre‐eclampsia and preterm birth, with potentially huge impact on short‐ and long‐term maternal and fetal wellbeing. Indeed, the introduction of such screening techniques in obstetrics has led to significant reductions in the incidence of certain conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in imaging techniques, medical genetics and clinical biology have enabled clinicians to screen for various adverse outcomes, such as aneuploidy, pre‐eclampsia and preterm birth, with potentially huge impact on short‐ and long‐term maternal and fetal wellbeing. Indeed, the introduction of such screening techniques in obstetrics has led to significant reductions in the incidence of certain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of detection improved with the introduction of sequential screening using first‐trimester ultrasound and first‐ as well as second‐trimester serum markers (90% detection), and subsequently improved even further with the advent of cell‐free DNA testing, which allowed screening as early as 10 weeks' gestation, with 99% sensitivity. These advances in screening have improved our ability to offer prenatal, or immediate neonatal, targeted therapy. To take another example, routine screening for pre‐eclampsia, with thorough maternal history‐taking, biochemical‐marker measurement and uterine artery Doppler assessment, has improved the prediction of this hypertensive disorder, thus facilitating the use of aspirin prophylaxis in high‐risk patients, a course of action which, when initiated prior to 16 weeks of gestation, has proved efficacious in the prevention of pre‐eclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…13 Alldred SK et al reported that meta-analysis of the six most frequently evaluated test combinations showed that a test strategy involving maternal age and a combination of first trimester NT and PAPP-A, and second trimester total hcG, uE3, AFP and Inhibin A significantly outperformed other test combinations that involved only one serum marker or NT in the first trimester, detecting about nine out of every 10 Down's syndrome pregnancies at a 5% false positive rate. 14 Alldred SK et al reported that meta-analysis of 12 best performing or frequently evaluated test combinations showed double and triple tests (involving AFP, uE3, total hcG, free hcG) significantly outperform individual markers, detecting six to seven out of every 10 Down's syndrome pregnancies at a 5% false positive rate.…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers suggest that AFP MoM ≤ 0.5 and β-hCG MoM≥2.5 can be used as suitable cut-off values for screening Down syndrome pregnancy (5). And others only use median of MoM (mMoM) as a quality control measure but do not include in the screening criteria (6)(7)(8). From our clinical experiences, we have found that MoM value has certain clinical significance.…”
Section: Introductionmentioning
confidence: 93%